2013
DOI: 10.1053/j.gastro.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of miR-224 and the Passenger Strand of miR-221 Increase MBD2, Suppressing Maspin and Promoting Colorectal Tumor Growth and Metastasis in Mice

Abstract: Background and Aims Little is known about functions of microRNA (miR) passenger strands (miR*), or their roles in tumor development or progression. We screened for miRs and miR* whose levels were altered in metastatic colorectal cancer (CRC) cells and human tumor samples, and investigated their targets and effects on cell function and tumor progression in mice. Methods We performed array-based profile analysis to identify miRs whose levels were increased more than 2-fold in metastatic (SW620) CRC cells, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 29 publications
1
76
1
Order By: Relevance
“…Chromatin IP assay was carried out as described previously. 31 Immunoprecipitated DNA was quantitated by real-time quantitative PCR. Primer sets were chosen to amplify approximately 100 to 150 base pairs on the promoter of SOCS3.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin IP assay was carried out as described previously. 31 Immunoprecipitated DNA was quantitated by real-time quantitative PCR. Primer sets were chosen to amplify approximately 100 to 150 base pairs on the promoter of SOCS3.…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR-224 during CRC initiation and progression remains controversial [15, 16, 17, 18, 19, 20, 21]: MiR-224 is overexpressed in inflammatory bowel disease-associated CRC [21], it promotes CRC tumor growth in mice by repressing PHLPP1 and PHLPP2 [19], and ectopic miR-224 expression decreases the chemoradiosensitivity of CRC [22], all of which suggests an oncogenic function. Yet, reports that methotrexate-resistant colon cancer cells express lower miR-224 [23], and that miR-224 suppresses tumor growth and metastasis in vivo [20] suggest that an opposite role in CRC may be true.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, reports that methotrexate-resistant colon cancer cells express lower miR-224 [23], and that miR-224 suppresses tumor growth and metastasis in vivo [20] suggest that an opposite role in CRC may be true. The latter study also showed lower miR-224 expression in metastatic CRC cell lines versus non-metastatic cell lines, and in metastatic tumors in the lung versus primary CRC tumors [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Of note, extensive deep RNA sequencing in failing human hearts identified miR-21* to be expressed in the human heart and increased during heart failure (41). Others have shown functional roles for star miRNAs also in other pathologies, such as colorectal and prostate cancer or obesity/metabolic syndrome (42)(43)(44). RNA deep sequencing studies in Drosophila melanogaster identified that a large number of miRNA* sequences are not degraded but are able to bind to Ago2-RISC complexes (45)(46)(47).…”
Section: Methodsmentioning
confidence: 99%